2016
DOI: 10.1177/0886260516665106
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation, Offense, or Private Issue? Guardians’ Perceptions and Self-Efficacy in Handling Girl Compensated Dating in Hong Kong

Abstract: Compensated dating (CD) has emerged as a global concern since the 1990s. Although considerable empirical research has been conducted to assess the patterns of and factors influencing CD, limited information is currently available on the attitudes of guardians (e.g., social workers, police officers, parents of students, and community representatives) in a Chinese community toward this issue. Using survey data collected from 962 guardians, the current study analyzes the guardians' perceptions of CD and their sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Specifically, Section 138b of the Sexual Offences Special Provisions Act (1998) penalises convicted offenders with imprisonment for a term of not less than 5 years and not exceeding 20 years (URT, 1998). In addition, previous studies have suggested a number of interventions to address and/or mitigate sexual offences, such as strengthening medico-legal linkages and legislative responses to help attain easy access to social, legal and medical services for victims (Densen-Gerber and Hutchinson, 1979;Kilonzo et al, 2009); seeking help and support from formal and/or informal service providers (Abeid et al, 2014;McCleary-Sills et al, 2016;Muganyizi et al, 2011;Sayem et al, 2013); and handling preferences among stakeholders such as parents, police officers, community leaders and social workers (Li et al, 2016). However, most case studies in Tanzania have concentrated on examining the barriers that victims encounter when trying to access support, help or services from service providers such as police and health facilities (Abeid et al, 2014;Kisanga et al, 2013).…”
Section: Social and Legal Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Section 138b of the Sexual Offences Special Provisions Act (1998) penalises convicted offenders with imprisonment for a term of not less than 5 years and not exceeding 20 years (URT, 1998). In addition, previous studies have suggested a number of interventions to address and/or mitigate sexual offences, such as strengthening medico-legal linkages and legislative responses to help attain easy access to social, legal and medical services for victims (Densen-Gerber and Hutchinson, 1979;Kilonzo et al, 2009); seeking help and support from formal and/or informal service providers (Abeid et al, 2014;McCleary-Sills et al, 2016;Muganyizi et al, 2011;Sayem et al, 2013); and handling preferences among stakeholders such as parents, police officers, community leaders and social workers (Li et al, 2016). However, most case studies in Tanzania have concentrated on examining the barriers that victims encounter when trying to access support, help or services from service providers such as police and health facilities (Abeid et al, 2014;Kisanga et al, 2013).…”
Section: Social and Legal Responsesmentioning
confidence: 99%
“…In addition, practitioners in the formal helping network are critical in protecting minors from sexual exploitation and assisting them in recovering from victimisation experiences. Social workers must first establish their own personal and professional attitudes and address their own complex emotions and prejudices, given that sexual exploitation of children and adolescents is a complex and controversial phenomenon (Li et al, 2016;Peled and Lugasi, 2015). The next step for social workers is to equip themselves with relevant knowledge and skills.…”
Section: Implications For Social Workmentioning
confidence: 99%